Hubungan Merokok dan Aktivitas Fisik dengan Kejadian Akne Vulgaris - Siti Rahmawati; Satya Wydya Yenny; Linosefa Linosefa (VitaMedica : Jurnal Rumpun Kesehatan Umum, 2024)
Background: Acne vulgaris is a chronic inflammation of the pilosebaceous follicle and its causes are multifactorial. Smoking causes changes in skin microcirculation, keratinocytes, fibroblasts and blood vessels. Physical activity can cause acne vulgaris because there is an increase in sweat secretion followed by sebum hypersecretion. Objective: This study aims to determine the relationship between smoking and physical activity with the incidence of acne vulgaris. Methods: This study used a cross-sectional design conducted in December 2021 at the Faculty of Medicine, Unand and the Griya Satya Clinic. The research population was male students of the Faculty of Medicine, Unand batch 2018. The method used total sampling method, there were 61 respondents in the age range of 19-22 years. The data obtained were primary data from a questionnaire and the diagnosis was confirmed by extraction of comedones. The analysis uses the chi-square test to determine the relationship between variables.Results: The results of statistical test using thetest chi-square showed that, there is no significant relationship between smoking habits and the incidence of acne vulgaris (p = 0.335), there is no significant relationship between physical activity habits and the incidence of acne vulgaris (p value = 0.851), there is no relationship significant relationship between smoking habits and physical activity with the incidence of acne (p value = 0.335). Conclusion: Medical students at the Faculty of Medicine, Andalas University, most of them had light smoking habit and most of them had moderate-to-heavy physical activity. And there is no relationship between smoking and physical activity toward the incidence of acne vulgaris.